Firearms and Violence: A Critical Review - Petrie, Carol V; Pepper, John V; Wellford, Charles F (National Academies Press, 2004)
For years proposals for gun control and the ownership of firearms have been among the most contentious issues in American politics. For public authorities to make reasonable decisions on these matters, they must take into account facts about the relationship between guns and violence as well as conflicting constitutional claims and divided public opinion. In performing these tasks, legislators need adequate data and research to judge both the effects of firearms on violence and the effects of different violence control policies. Readers of the research literature on firearms may sometimes find themselves unable to distinguish scholarship from advocacy. Given the importance of this issue, there is a pressing need for a clear and unbiased assessment of the existing portfolio of data and research. Firearms and Violence uses conventional standards of science to examine three major themes - firearms and violence, the quality of research, and the quality of data available. The book assesses the strengths and limitations of current databases, examining current research studies on firearm use and the efforts to reduce unjustified firearm use and suggests ways in which they can be improved.